2023
DOI: 10.3390/cancers15153984
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of Red Blood Cell Distribution Width (RDW) in Endometrial Cancer: A Retrospective Single-Center Experience from Korea

Abstract: Background: Red blood cell distribution width (RDW) is a standard parameter of complete blood count and indicates the variability in red blood cell size. This study aimed to determine whether preoperative RDW can be used to predict the recurrence and prognosis of endometrial carcinoma. Methods: The medical records of 431 patients diagnosed with endometrial carcinoma were retrospectively reviewed between May 2006 and June 2018. In addition to RDW, the clinicopathological factors, survival curves, and prognoses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Specifically, the percentages of patients with high RDW were 14.4% in stage I, 32.2% in stage II, 37.6% in stage III, and 39.4% in stage IV. This suggests a potential role for RDW as a prognostic marker in EC [17].…”
Section: Discussionmentioning
confidence: 84%
“…Specifically, the percentages of patients with high RDW were 14.4% in stage I, 32.2% in stage II, 37.6% in stage III, and 39.4% in stage IV. This suggests a potential role for RDW as a prognostic marker in EC [17].…”
Section: Discussionmentioning
confidence: 84%
“…Complete blood count-based biomarkers have been shown to correlate well with clinical outcomes in numerous chronic [ 5 , 6 , 7 , 8 , 9 , 10 ], infectious [ 11 , 12 , 13 , 14 , 15 ], and surgical conditions [ 16 , 17 , 18 , 19 , 20 ], as well as in cancer [ 21 , 22 , 23 , 24 , 25 , 26 ]. In particular, the potential role of the red cell distribution width (RDW), a biomarker of the heterogeneity of red blood cells’ size, in predicting adverse events and survival currently represents a topic of intense research in numerous clinical conditions [ 27 , 28 ], including malignancies such as colorectal cancer [ 29 , 30 , 31 ], esophageal cancer [ 32 , 33 ], lung cancer [ 34 , 35 ], breast cancer [ 36 , 37 ], and other malignancies [ 38 , 39 , 40 , 41 , 42 ]. In addition, several studies have shown that alterations in the RDW correlate with liver function and prognosis in numerous hepatic cancer-predisposing conditions, such as hepatitis B, chronic liver disease, and fibrosis [ 43 , 44 , 45 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tumors affecting the bone marrow, as seen in myelodysplastic syndromes and leukemia, can disrupt the normal production of RBCs, manifesting as changes in the RDW and Hb levels, ultimately influencing the Hb/RDW ratio [51]. Furthermore, advanced tumor stages and larger tumor sizes have been linked to changes in the RDW, offering insights into tumor characteristics and progression [52]. Therapies like chemotherapy and radiation, which directly affect bone marrow and the production of RBCs, contribute to the composite nature of the Hb/RDW ratio, making it a valuable indicator of a patient's overall condition [53,54].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, advanced tumor stages and larger tumor sizes have been linked to changes in the RDW, offering insights into tumor characteristics and progression [52]. Therapies like chemotherapy and radiation, which directly affect bone marrow and the production of RBCs, contribute to the composite nature of the Hb/RDW ratio, making it a valuable indicator of a patient's overall condition [53,54].…”
Section: Introductionmentioning
confidence: 99%